Modified AES with Matrices Selective Block Cipher on Image Encryption - Barja Sanjaya, Muhammad; Adolf Telnoni, Patrick (International Journal of Engineering and Technology, 2019)
Advanced Encryption Standard (AES) is one of symmetric cryptography which its operation is conducted in cipher block mode. Meanwhile the computation operation is in cipher block mode, AES takes high cost of computation to process the data. Moreover nowadays the data size to process has been bigger, such as image. Because of this, it appears several questions for AES cryptography performance to implement. Several designs of methods that have been studied and conducted namely selective bit plane in 2002 and partially encryption in 2013 were still in high cost for computation. Thus, a new design or method is proposed to cut off the high cost of computation in time processing and memory consumption. In this study, it is proposed matrices selective block cipher which its process operates the object of area in an image to be encrypted exactly. The operation which is conducted while encrypting the selected area in image is only on one of the layers, it also involves random number Blum-Blum-Shub and Chaotic Function for initializating the key. Based on the data result of experimental tests, it is achieved an optimization for the proposed method as big as 28.61197 times faster instead of applying combination partially encryption and selective bit plane in a usual method and it also takes an additional memory comsumption as big as 0.168545%.Â